Experts’ consensus on the definition and management of high risk multiple myeloma - Marcon, Chiara; Simeon, Valentina; Deias, Paola; Facchin, Gabriele; Corso, Alessandro; Derudas, Daniele; Montefusco, Vittorio; Offidani, Massimo; Petrucci, Maria Teresa; Zambello, Renato; Stocchi, Raffaella; Fanin, Renato; et al. (Frontiers in Oncology, 2023)
High risk multiple myeloma (HRMM) at diagnosis is currently recognized according to the Revised International Staging System (R-ISS) which was set up in 2015. Since then, new clinical and biological prognostic factors have been developed, which could implement the definition of High Risk (HR) category. We conducted a survey in order to identify which additional parameters, both clinical and biological, are considered more useful for the clinical practice and to evaluate if the management of Multiple Myeloma (MM) should change on the basis of the risk category. A questionnaire, consisting of 8 statements, was submitted to 6 Italian experts, from the European Myeloma Network (EMN) Research Italy, using the Delphi method. The colleagues were asked to answer each question using a scale between 0 and 100. If a statement did not reach at least 75 out of 100 points from all the participants, it was rephrased on the basis of the proposal of the experts and resubmitted in a second or further round, until a consensus was reached among all. From the first round of the survey a strong consensus was reached regarding the opportunity to revise the R-ISS including chromosome 1 abnormality, TP53 mutation or deletion, circulating plasma cells by next generation flow and extramedullary plasmacytomas. No consensus was reached for the definition of “double hit” MM and for the application in clinical practice of treatment strategies based on the risk category. In the second round of the Delphi questionnaire, “double-hit” MM was recognized by the association of at least two high-risk cytogenetic or molecular abnormalities. Moreover, the experts agreed to reserve an intensified treatment only to specific conditions, such as plasma cell leukaemia or patients with multiple extramedullary plasmacytomas, while they admitted that there are not sufficient real word data in order to modify treatment on the basis of MRD assessment in clinical practice. This survey suggests that the definition of HRMM should be implemented by additional clinical and biological risk factors, that will be useful to guide treatment in the future.